Fishing Lessons - Bridwell, Norman; Nang Chan Yeema (New York, USA Scholastic Inc., 2003)
Charley promises to teach Emily Elizabeth how to fish. But every day something else comes up. Will Emily Elizabeth and Clifford have to teach themselves how to fish?
Keywords: Story Collection